Analisis dan Perancangan Sistem Keuangan pada SMAK St. Augustinus Kediri - Agus Kristianto; Heri Abijono; Hartati Dyah Wahyuningsih (Sekolah Tinggi Manajemen Informatika dan Komputer AUB - Indonesia, 2026)
A common problem in the financial administration department of SMAK St. Augustinus Kediri is the lack of work efficiency in terms of time and effort, and the resulting reports, from income to expenditure, are still inaccurate. The current system is computerized, but in the administration department, each officer still processes data independently according to their resource capabilities. As a result, the accuracy of the data produced for reports or information needed by the Principal and the foundation is not well integrated. The result of this study is an analysis to produce a new system design that handles financial administration to process payment transaction data from students and expenditure transactions. The researcher then reported the results of the analysis and design of the new system to the foundation and the Principal to get recommendations for implementing the new system in the future.